Implementasi dan Evaluasi Cloudflare Zero Trust untuk Akses Sistem Keuangan pada PT Leka Mandiri - Ahnaf Musyaffa Bisyri; April Rustianto; Zaki Imamuddin (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
In the digital era, fast, secure access to financial information is essential for companies to enhance operational efficiency and improve business decision-making. PT Leka Mandiri initially operated an offline financial system, limiting operational flexibility, especially for transaction processing outside working hours. To enable online access, a public IP address is ideally required; however, obtaining one is relatively expensive. As a solution, the company implemented Cloudflare Zero Trust, enabling secure access to the financial system without requiring a public IP address. This study aims to evaluate the effectiveness of Zero Trust in overcoming access limitations without a public IP and its impact on PT Leka Mandiri’s operational flexibility. The test results indicate that the implemented system successfully handled financial transactions with a 100% success rate across various transaction types. Additionally, the system provides enhanced security through identity-based access control and real-time security analytics. Thus, Cloudflare Zero Trust has been proven to be an effective and economical solution for companies to improve accessibility and operational efficiency without requiring a public IP address.